Modified carbon nitride, preparation method and application thereof, and method for removing toluene

CN122912901APending Publication Date: 2026-10-16CHONGQING UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611402450.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

以TiO2为代表的光催化剂虽已广泛应用于VOCs去除,但其禁带宽度约为3.2eV,仅能响应占太阳光谱不足5%的紫外光,在车内弱光照、高湿度的环境中光催化活性大幅下降,难以满足实际应用需求

Benefits of technology

[0015] This invention provides a method for preparing modified carbon nitride, comprising the following steps: mixing dicyandiamide and urea and then calcining the mixture to obtain the modified carbon nitride; the mass ratio of dicyandiamide to urea is 1:2.8~3.2. This invention, by simply controlling the mass ratio of dicyandiamide to urea, enables the prepared modified carbon nitride to have fully exposed active sites and a significantly enhanced π-conjugated delocalized electronic structure, while also exhibiting a high specific surface area. The modified carbon nitride prepared according to the method provided by this invention can effectively enrich low concentrations of toluene in the atmosphere and can be degraded under visible light conditions. The preparation method of this invention is simple, and the obtained modified carbon nitride has good biocompatibility and stability, making it applicable to interior functional materials such as automotive sunshade films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912901A_ABST
    Figure CN122912901A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of photocatalytic materials, and particularly relates to modified carbon nitride, a preparation method and application thereof, and a method for removing toluene. The preparation method of the modified carbon nitride provided by the application comprises the following steps: mixing dicyandiamide and urea, and then calcining to obtain the modified carbon nitride; and the mass ratio of the dicyandiamide to the urea is 1:2.8-3.2. By simply regulating the mass ratio of the dicyandiamide to the urea, the modified carbon nitride prepared has fully exposed active sites and significantly enhanced pi-conjugated delocalized electronic structures, and the modified carbon nitride prepared has a relatively high specific surface area; the modified carbon nitride prepared according to the preparation method provided by the application can effectively enrich low-concentration toluene in the atmosphere and can be degraded under visible light. The preparation method is simple, the modified carbon nitride obtained has good biocompatibility and stability, and can be applied to automotive sunshade films and other interior functional materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photocatalytic materials technology, specifically relating to a modified carbon nitride, its preparation method and application, and a method for removing toluene. Background Technology

[0002] Volatile organic compound (VOC) pollution in vehicles has become a significant environmental problem affecting the health of drivers and passengers. As of the end of June 2024, the number of vehicles in China had reached 440 million. Toluene and other benzene compounds, as common solvent residues in automotive interiors and adhesives, are continuously released in the enclosed vehicle cabin. Long-term exposure can damage the human central nervous system and respiratory system.

[0003] Currently, VOCs treatment technologies mainly include adsorption, combustion, biological methods, and photocatalytic oxidation. Among these, photocatalytic oxidation has attracted much attention due to its green, efficient, and pollution-free nature. While photocatalysts, such as TiO2, are widely used for VOCs removal, their band gap of approximately 3.2 eV means they can only respond to ultraviolet light, which accounts for less than 5% of the solar spectrum. Their photocatalytic activity drops significantly in low-light, high-humidity environments inside vehicles, making them unsuitable for practical applications. Graphitic carbon nitride (g-C3N4, CN), as a non-metallic polymer semiconductor material, possesses advantages such as a suitable band gap (approximately 2.7 eV), good visible light responsiveness, stable physicochemical properties, and wide availability of raw materials, showing broad application prospects in photocatalytic organic pollutant removal and green energy conversion. However, CN prepared using existing methods still suffers from inherent defects such as severe photogenerated carrier recombination and insufficient exposure of active sites, resulting in the inability to effectively enrich low-concentration toluene and overall low removal efficiency. Summary of the Invention

[0004] In view of this, the present invention provides a modified carbon nitride, its preparation method and application, and a method for removing toluene. The modified carbon nitride prepared according to the preparation method provided by the present invention has fully exposed active sites and a significantly enhanced π-conjugated delocalized electronic structure, which can effectively adsorb low concentrations of toluene in the atmosphere.

[0005] To address the aforementioned technical problems, this invention provides a method for preparing modified carbon nitride, comprising the following steps: Dicyandiamide and urea are mixed and calcined to obtain the modified carbon nitride; the mass ratio of dicyandiamide to urea is 1:2.8~3.2.

[0006] Preferably, the mixing is carried out under grinding conditions, and the grinding time is 13-17 minutes.

[0007] Preferably, the calcination temperature is 530~570℃ and the time is 3.8~4.2h.

[0008] Preferably, the heating rate to the calcination temperature is 2.3~2.7℃ / min.

[0009] The present invention also provides modified carbon nitride prepared by the preparation method described above, with a specific surface area of ​​27-29 m². 2 / g, with a tubular morphology.

[0010] The present invention also provides the application of the modified carbon nitride described above in the removal of toluene from gases.

[0011] The present invention also provides a method for removing toluene, comprising the following steps: Modified carbon nitride was placed in a toluene-containing atmosphere for adsorption under dark conditions, and then subjected to photocatalytic oxidation degradation under light conditions to obtain regenerated modified carbon nitride and gas after toluene removal. The modified carbon nitride is the modified carbon nitride described in the above technical solution.

[0012] Preferably, the concentration of toluene in the toluene-containing atmosphere is 0.3~2 ppm; The mass ratio of the modified carbon nitride to the volume ratio of the toluene-containing atmosphere is 100 mg: 0.8~1.2 L.

[0013] Preferably, the adsorption time is 25-35 minutes.

[0014] Preferably, the light source is visible light, and the light intensity is 280~320mW / cm². 2 ; The photocatalytic oxidation degradation time is 110~130 min.

[0015] This invention provides a method for preparing modified carbon nitride, comprising the following steps: mixing dicyandiamide and urea and then calcining the mixture to obtain the modified carbon nitride; the mass ratio of dicyandiamide to urea is 1:2.8~3.2. This invention, by simply controlling the mass ratio of dicyandiamide to urea, enables the prepared modified carbon nitride to have fully exposed active sites and a significantly enhanced π-conjugated delocalized electronic structure, while also exhibiting a high specific surface area. The modified carbon nitride prepared according to the method provided by this invention can effectively enrich low concentrations of toluene in the atmosphere and can be degraded under visible light conditions. The preparation method of this invention is simple, and the obtained modified carbon nitride has good biocompatibility and stability, making it applicable to interior functional materials such as automotive sunshade films. Attached Figure Description

[0016] Figure 1 SEM images of the modified carbon nitride prepared in Example 1 and Comparative Examples 1-3; Figure 2 The XRD patterns of the modified carbon nitride prepared in Example 1 and Comparative Examples 1-3 are shown below. Figure 3 Fourier transform infrared spectra of the modified carbon nitride prepared in Example 1 and Comparative Examples 1-3; Figure 4 The UV-Vis diffuse reflectance spectra of the modified carbon nitride prepared in Example 1 and Comparative Examples 1-3 are shown. Figure 5 Tauc diagrams of the modified carbon nitride prepared in Example 1 and Comparative Examples 1-3; Figure 6 The results of photocurrent response and electrochemical impedance of the modified carbon nitride prepared in Examples 1 and Comparative Examples 1-3 are shown, where (a) is the photocurrent response of Examples 1 and Comparative Examples 1-3, (b) is the electrochemical impedance spectrum of Examples 1 and Comparative Examples 1-3, and (c) is the photoluminescence spectrum of Examples 1 and Comparative Example 1. Figure 7 The nitrogen adsorption-desorption curves of the modified carbon nitride prepared in Example 1 and Comparative Examples 1-3 are shown. Figure 8 The bar chart shows the comparison of toluene removal rates of the modified carbon nitride prepared in Example 1 and Comparative Examples 1-3. Figure 9 A bar chart comparing the removal rates of toluene by cyclic removal using modified carbon nitride prepared in Example 1; Figure 10 The results of the biosafety test of the modified carbon nitride prepared in Example 1 are shown. The left side shows the survival of the strains cultured in the medium without modified carbon nitride, and the right side shows the survival of the strains in the medium containing modified carbon nitride. Detailed Implementation

[0017] This invention provides a method for preparing modified carbon nitride, comprising the following steps: Dicyandiamide and urea were mixed and then calcined to obtain the modified carbon nitride.

[0018] In this invention, unless otherwise specified, all materials are commercially available products.

[0019] In this invention, the mass ratio of dicyandiamide to urea is 1:2.8~3.2, specifically 1:3.

[0020] In this invention, the mixing can be carried out under grinding conditions, and the grinding time can be 13-17 minutes, specifically 15 minutes. This invention does not have special requirements for the grinding speed, as long as it ensures thorough mixing of the materials.

[0021] In this invention, the calcination temperature can be 530~570℃, specifically 550℃; the heating rate to the required calcination temperature can be 2.3~2.7℃ / min, specifically 2.5℃ / min; and the calcination time can be 3.8~4.2h, specifically 4h. In this invention, the calcination can be carried out in a muffle furnace. This invention achieves in-situ pore formation by controlling the mass ratio of dicyandiamide to urea during calcination and utilizing the gas released from urea decomposition. Simultaneously, it synergistically optimizes the π-conjugated structure to expand the number of delocalized electrons, thus preparing modified carbon nitride materials with both high specific surface area and excellent photocatalytic activity.

[0022] This invention can simultaneously improve the specific surface area of ​​modified carbon nitride and optimize the π-conjugated electronic structure by simply adjusting the precursor ratio of dicyandiamide and urea. The preparation method is simple and controllable, and does not require complex templates or post-processing steps.

[0023] In this invention, the calcination process further includes: cooling the calcined product to room temperature and then grinding it to obtain the modified carbon nitride; the room temperature can be 20~35℃, or 25~30℃; the cooling method can be furnace cooling. This invention transforms the calcined bulk material into powder through grinding, and this invention has no special requirements on the particle size of the ground product.

[0024] The present invention also provides modified carbon nitride prepared by the preparation method described above, with a specific surface area of ​​27-29 m². 2 / g, which can be specifically 28m 2 / g. In this invention, the modified carbon nitride is tubular, and the modified carbon nitride is modified graphitic carbon nitride.

[0025] The modified carbon nitride obtained by this invention possesses both a high specific surface area and an enhanced π-conjugated delocalized electronic structure. The high specific surface area provides abundant active sites, which is beneficial for the effective enrichment of low-concentration toluene. The optimized π-conjugated electronic structure promotes the separation and migration of photogenerated carriers, significantly improving photocatalytic oxidation activity. The two work synergistically to achieve a cascade effect of adsorption-oxidation, realizing the efficient removal of low-concentration toluene from the atmosphere (e.g., in-vehicle air). The modified carbon nitride obtained by this invention has good biocompatibility and high stability.

[0026] The present invention also provides the application of the modified carbon nitride described above in the removal of toluene from gases.

[0027] This invention achieves precise control over the π-conjugated structure of materials by adjusting the ratio of raw materials, thereby optimizing the morphology and enhancing the number of delocalized electrons. During the photocatalytic degradation of toluene, the synergistic effect of morphology optimization and enhanced π-electron delocalization significantly improves the overall efficiency of the adsorption-oxidation cascade process, thus greatly enhancing toluene removal performance. Furthermore, this material exhibits good biocompatibility and high stability while maintaining high catalytic performance, making it suitable for use as interior functional materials such as automotive sunshade films, and effectively removing toluene, a volatile organic pollutant, from automotive cabins.

[0028] The present invention also provides a method for removing toluene, comprising the following steps: Modified carbon nitride was placed in a toluene-containing atmosphere for adsorption under dark conditions, and then subjected to photocatalytic oxidation degradation under light conditions to obtain regenerated modified carbon nitride and gas after toluene removal. The modified carbon nitride is the modified carbon nitride described in the above technical solution.

[0029] In this invention, the concentration of toluene in the toluene-containing atmosphere can be 0.3~2ppm, specifically 0.3ppm, 0.5ppm, 1.5ppm or 2ppm; the mass ratio of the modified carbon nitride to the volume ratio of the toluene-containing atmosphere can be 100mg:0.8~1.2L, specifically 100mg:1L.

[0030] This invention does not have special requirements regarding the method of forming the dark state; conventional methods in the art are sufficient. In this invention, the adsorption time can be 25-35 minutes, specifically 30 minutes. This invention can enrich low concentrations of toluene in the atmosphere through adsorption, facilitating subsequent catalytic oxidation and degradation.

[0031] In this invention, the light source can be visible light, which can be provided by a xenon lamp; the intensity of the light can be 280~320mW / cm². 2 Specifically, it can be 300mW / cm 2 The photocatalytic oxidation degradation time can be 110-130 min, specifically 120 min. This invention, under illumination, can activate oxygen in the air to achieve photocatalytic oxidation, thereby realizing the catalytic oxidation degradation of pollutants (toluene) in modified carbon nitride that has adsorbed toluene.

[0032] In this invention, the regenerated modified carbon nitride has good stability and can be recycled.

[0033] To further illustrate the present invention, the technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0034] Example 1 2.5g of dicyandiamide and 7.5g of urea were mixed and ground for 15 minutes to ensure uniform mixing. The mixed powder was collected and transferred to a covered crucible, heated to 550℃ in a muffle furnace at a heating rate of 2.5℃ / min, and held at that temperature for 4 hours before being naturally cooled to room temperature (25℃). The product was collected and ground to obtain powdered modified carbon nitride, denoted as CN(1:3).

[0035] Comparative Example 1 Modified carbon nitride was prepared according to the method in Example 1, except that the amount of dicyandiamide was adjusted from 2.5g to 5g and the amount of urea was adjusted from 7.5g to 5g; the resulting modified carbon nitride was denoted as CN(2:2).

[0036] Comparative Example 2 Modified carbon nitride was prepared according to the method in Example 1, except that dicyandiamide was not added (the amount of dicyandiamide was adjusted from 2.5g to 0g), and the amount of urea was adjusted from 7.5g to 10g; the resulting modified carbon nitride was denoted as CN(0:4).

[0037] Comparative Example 3 Modified carbon nitride was prepared according to the method in Example 1, except that 2.5g of dicyandiamide and 7.5g of urea were replaced with 10g of dicyandiamide; the resulting modified carbon nitride was denoted as CN(4:0).

[0038] The modified carbon nitride prepared in Example 1 and Comparative Examples 1-3 were examined by scanning electron microscopy (SEM), and the resulting SEM images are shown below. Figure 1 As shown. By Figure 1 It can be seen that CN(0:4), CN(2:2) and CN(4:0) exhibit a bulk structure, while CN(1:3) exhibits a tubular structure, indicating that the preparation method provided by this invention (adjusting the mass ratio of dicyandiamide to urea) affects the morphology of the modified carbon nitride.

[0039] X-ray diffraction and infrared spectroscopy were performed on the modified carbon nitride prepared in Example 1 and Comparative Examples 1-3. The obtained XRD patterns are shown below. Figure 2 As shown, the obtained Fourier transform infrared spectrum is as follows: Figure 3 As shown. By Figure 2 and 3 It can be seen that all four materials exhibit typical carbon nitride structures; however, although the phase composition and structure are almost identical, the diffraction peaks of carbon nitride at 12.98° (100) and 27.42° (002) show significant differences, indicating that the preparation method provided by the present invention can effectively adjust the interlayer and in-plane stacking arrangement of carbon nitride, thereby optimizing the π-conjugated delocalized electronic structure.

[0040] Figure 4The UV-Vis diffuse reflectance spectra of the modified carbon nitride prepared in Example 1 and Comparative Examples 1-3 are shown below. Figure 5 The Tauc diagrams are for the modified carbon nitride prepared in Example 1 and Comparative Examples 1-3. Figure 4 and Figure 5 It can be seen that there are significant differences in the light absorption activities of CN(0:4), CN(1:3), CN(2:2), and CN(4:0), especially in the π-π group. Electronic transitions and band gap width were effectively adjusted. With the addition of dicyandiamide, the band gap width gradually decreased from 3.06 eV to 2.98 eV, indicating that the preparation method provided by this invention can directly control the π-conjugated delocalized electronic structure of carbon nitride, thereby controlling the photogenerated carrier migration barrier and preparing for the subsequent degradation and removal of adsorbed pollutants.

[0041] Photoelectric property testing: The photocurrent response and electrochemical impedance of the modified carbon nitride prepared in Example 1 and Comparative Examples 1-3 were tested using a three-electrode system as follows: Figure 6 As shown, (a) is the photocurrent response of Example 1 and Comparative Examples 1-3, (b) is the electrochemical impedance spectroscopy of Example 1 and Comparative Examples 1-3, and (c) is the photoluminescence spectrum of Example 1 and Comparative Example 1. Figure 6 It can be seen that, compared with Comparative Example 2 (CN(0:4)) containing only urea and Comparative Example 3 (CN(4:0)) containing only dicyandiamide, the modified carbon nitride (CN(1:3) and CN(2:2)) prepared by the mixed precursor (urea + dicyandiamide) exhibit higher photocurrent response and lower electrochemical impedance. This is attributed to the optimal control of precursor mixing on the adjustment of the π-conjugated delocalized electronic structure of carbon nitride, which improves light absorption activity while suppressing recombination of photogenerated carriers. Compared with CN(2:2), CN(1:3) exhibits a lower emission peak in the steady-state photoluminescence spectrum. Figure 6 (c) indicates that CN(1:3) has a higher photogenerated carrier migration efficiency and its direct recombination of photogenerated carriers is significantly suppressed, which is attributed to the simultaneous optimization and improvement of its morphology and π-conjugated delocalized electronic structure.

[0042] Specific surface area testing and applications of adsorption-photo-oxidation cascade for toluene removal: The nitrogen adsorption-desorption curves for CN(0:4), CN(1:3), CN(2:2), and CN(4:0) are shown below. Figure 7 As shown, their specific surface areas are 59.5 m². 2 / g, 28.0m 2 / g, 8.8m 2 / g and 6.0m 2 / g.

[0043] 100 mg of the modified carbon nitride prepared in Example 1 and Comparative Examples 1-3 were placed in a 1 L sealed transparent reactor containing 1.5 ppm toluene. After adsorption equilibrium was achieved in the dark (30 min), the reactor was then placed under a light intensity of 300 mw / cm². 2 Toluene was removed by photocatalytic oxidation degradation under visible light for 120 min. Gas chromatography was used to quantitatively analyze the toluene at different time points, obtaining the toluene adsorption rate at adsorption equilibrium and the toluene removal rate after treatment. The results are listed in Table 1.

[0044] Table 1. Adsorption and degradation results of toluene by modified carbon nitride prepared in Example 1 and Comparative Examples 1-3.

[0045] Draw a bar chart based on Table 1, such as... Figure 8 As shown.

[0046] Combined with Table 1, Figure 7 and Figure 8 It can be seen that although CN(0:4) has a higher specific surface area, its macroscopic morphology and π-conjugated delocalized electronic structure were not effectively modulated, resulting in unsatisfactory activity in both the adsorption stage (19.32%) and the subsequent photo-oxidation stage for toluene removal. In contrast, CN(1:3) material achieved a stronger adsorption (27.63%)-photo-oxidation synergistic toluene removal efficiency (92.45%). This enhanced adsorption-photo-oxidation synergistic effect is attributed to the optimal control of the precursor, which enabled CN(1:3) to obtain a special tubular morphology and suitable specific surface area, which is conducive to the enrichment of low-concentration toluene inside the vehicle. Meanwhile, the simultaneously optimized π-conjugated electronic structure promoted the separation and migration of photogenerated carriers, significantly improving the activity of subsequent cascaded photocatalytic oxidation. The synergistic effect of these two factors ultimately achieved efficient removal of low-concentration toluene from the vehicle interior.

[0047] Continuous recycling and biosafety assessment of CN (1:3) The modified carbon nitride CN (1:3) prepared in Example 1 was subjected to five consecutive cycles of use. The specific method was as follows: 100 mg of the modified carbon nitride prepared in Example 1 was placed in a closed transparent reactor with a toluene concentration of 1.5 ppm and a volume of 1 L. After adsorption equilibrium was achieved under dark conditions (30 min), the reactor was then placed under a light intensity of 300 mw / cm². 2 Toluene was removed by photocatalytic oxidation degradation under visible light for 120 min. The concentration of toluene after the reaction was quantitatively analyzed by gas chromatography, and the results are listed in Table 2.

[0048] Table 2. Toluene removal rate of modified carbon nitride cycled adsorption and degradation in Example 1.

[0049] Draw a bar chart based on Table 2, such as... Figure 9 As shown.

[0050] Table 2 and Figure 9 The results show that, during long-term operation, the modified carbon nitride provided by this invention maintains a removal efficiency of over 85% for the volatile organic pollutant toluene, demonstrating excellent catalytic stability and good recyclability.

[0051] Using *Escherichia coli* and *Staphylococcus aureus* as model organisms, the biosafety of the modified carbon nitride CN (1:3) prepared in Example 1 was tested. The specific procedure was as follows: the prepared modified carbon nitride CN (1:3) was placed in a liquid culture medium containing *Escherichia coli* and *Staphylococcus aureus*. The strains were first activated and cultured, and then plated to detect the survival and reproduction of each strain. The test results were compared with those of strains cultured without modified carbon nitride CN (1:3).

[0052] The results are as follows Figure 10 As shown, the left side represents the survival rate of strains cultured in a medium without modified carbon nitride, while the right side represents the survival rate of strains cultured in a medium containing modified carbon nitride. Figure 10 It can be seen that the growth and proliferation of both bacteria were not significantly affected in an environment rich in CN (1:3), confirming that the material has good biocompatibility. These results indicate that CN (1:3) can be applied to interior materials such as automotive sunshade films, effectively and safely removing volatile organic pollutants from vehicle interiors.

[0053] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing modified carbon nitride, characterized in that, Includes the following steps: Dicyandiamide and urea were mixed and then calcined to obtain the modified carbon nitride. The mass ratio of dicyandiamide to urea is 1:2.8~3.

2.

2. The preparation method according to claim 1, characterized in that, The mixing is carried out under grinding conditions, and the grinding time is 13-17 minutes.

3. The preparation method according to claim 1, characterized in that, The calcination temperature is 530~570℃, and the time is 3.8~4.2h.

4. The preparation method according to claim 3, characterized in that, The heating rate to the required calcination temperature is 2.3~2.7℃ / min.

5. The modified carbon nitride prepared by the preparation method according to any one of claims 1 to 4, characterized in that, Specific surface area is 27~29m² 2 / g, with a tubular morphology.

6. The use of the modified carbon nitride according to claim 5 in the removal of toluene from gases.

7. A method for removing toluene, characterized in that, Includes the following steps: Modified carbon nitride was placed in a toluene-containing atmosphere for adsorption under dark conditions, and then subjected to photocatalytic oxidation degradation under light conditions to obtain regenerated modified carbon nitride and gas after toluene removal. The modified carbon nitride is the modified carbon nitride as described in claim 5.

8. The method for removing toluene according to claim 7, characterized in that, The concentration of toluene in the toluene-containing atmosphere is 0.3~2 ppm; The mass ratio of the modified carbon nitride to the volume ratio of the toluene-containing atmosphere is 100 mg: 0.8~1.2 L.

9. The method for removing toluene according to claim 7 or 8, characterized in that, The adsorption time is 25-35 minutes.

10. The method for removing toluene according to claim 7, characterized in that, The light source is visible light, and the light intensity is 280~320mW / cm². 2 ; The photocatalytic oxidation degradation time is 110~130 min.